Pengembangan Lembar Kerja Siswa Etnomatematika Jajanan Pasar Tradisional Kota Pontianak Pada Materi Bangun Ruang Sisi Datar - Cristhoper Noveno Ambertaso Putra; Muchtadi , Muchtadi; Hartono, Hartono (Lembaga Pengembangan Kinerja Dosen, 2022)
This research aims to produce learning media for the Ethnomathematics Student Worksheet on Traditional Market Snacks in Pontianak City on the flat-sided building material that reaches the level of validity, practicality, and effectiveness. This study uses a 4D design model, which is modified into 3D, namely define (definition), design (design), development (development), without using the fourth stage, namely disseminate, because this refers to the initial goal of this research is to develop valid, practical and effective media contained in the third step of the development of this model, namely development. The subjects in this study were students of class VIII SMP Suster Pontianak with a total of 20 students. The instruments used in this study were validation sheets, questionnaires, and test questions. Based on the results of the first study, the validation of the Ethnomathematics Student Worksheet with an average value of 84,76% from expert activities was very valid with a very good category. The second is the value of practicality, seen from the value of the questionnaire filled in by the teacher, the percentage is 97% with very practical criteria. to see the effectiveness of the ethnomathematics-based student worksheet learning media compared to the Likert scale index, with a percentage of 81.11% in the very effective criteria.